Pyrrolidine Dithiocarbamate Might Mitigate Radiation-Induced Heart Damage at an Early Stage in Rats - Wu, Yajing; Liu, Lina; Lv, Shengliang; Wang, Yi; Wang, Shuai; Wang, Sheng; Zhang, Jiandong; Wang, Jun (Frontiers in Pharmacology, 2022)
Objective To investigate whether pyrrolidine dithiocarbamate( PDTC) can attenuate heart damage caused by irradiation and the potential mechanisms. Methods Twenty-one adult male Sprague-Dawley rats were randomized into control, irradiation and PDTC plus irradiation group. Hearts were irradiated with a single fraction of 20.0 Gy. Rats received intraperitoneal injection of PDTC. Echocardiography was performed at the 14th day post-irradiation. Morphological damage was observed by Hematoxylin-eosin stain and Masson’s trichrome stain. Collagen volume fraction (CVF) was applied for semi-quantitative analysis. The protein levels were analyzed by western blot. Their mRNA levels were determined by quantitative real-time PCR. Results No significant damage to structure and function of left ventricular was induced at very early stage. Compared with irradiation group, myocardial edema was alleviated in PDTC plus irradiation group, accompanied by mitigated myocardial interstitial inflammation infiltration. The values of CVF were 9.99±0.32% and 22.05±0.21% in PDTC plus irradiation group and irradiation group (P＜0.05). The protein and mRNA expression of P50, P65, and HIF-1α were down-regulated after treatment with PDTC (P＜0.05), but there was only a declining trend in protein and mRNA expression level of CTGF. The protein expression of COL-I in PDTC plus irradiation group was lower than that in irradiation group (P＜0.05), and COL-1 mRNA had a trend of down-regulation. Conclusion PDTC could alleviate myocardial cell edema, partial myocardial cell rupture, inflammation infiltration and pro-fibrotic change at very early stage in rat radiation-induced heart damage model by inhibiting the activation of NF-κB and hypoxia-inducible factor-1α (HIF-1α).